PENGARUH MOTIVASI DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA DI PEKANBARU - Sukriani, Nurul (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
This study aimed to analyze the influence of motivation, and family environment of the interest in entrepreneurship on Pekanbaru . Data analysis method used is qualitative and quantitative, data sources using primary and secondary in the form of questionnaires, interviews, and documentation. The population in this study were students who were interesting on business in Pekanbaru. For the population and sample because the number of population is not known for certain, then using the formula with the Wibisono method and obtained a sample size of 97 people. The results showed that there is significant influence between motivation, and family environment against the interests of students in entrepreneurship . Partially also found to influence the motivation, and family environment to be motivational variables that,,most influence on student interest in entrepreneurship